2002
DOI: 10.1128/jcm.40.8.3032-3034.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Infection Due to Imipenem-Resistant Bacteroides fragilis Associated with a Totally Implantable Venous Port

Abstract: Four patients in an oncology ward developed Bacteroides fragilis bacteremia over a 12-day period. Crossinfection between two of them, due to an imipenem-resistant strain, was demonstrated by epidemiological investigation and genotypic typing methods (arbitrarily primed PCR fingerprinting and nucleotide sequencing of the cfiA genes and upstream IS1186/IS1168 elements).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The fact that ®ve samples were taken from one patient might imply that the same strain has been isolated several times. Similar ®ndings indicating a spread of imipenem-resistant B. fragilis strains between hospitalized patients were recently reported by Arpin et al [26]. It seems that low-level resistance to imipenem is becoming more prevalent and resistance is even seen in species other than B. fragilis.…”
Section: Discussionsupporting
confidence: 87%
“…The fact that ®ve samples were taken from one patient might imply that the same strain has been isolated several times. Similar ®ndings indicating a spread of imipenem-resistant B. fragilis strains between hospitalized patients were recently reported by Arpin et al [26]. It seems that low-level resistance to imipenem is becoming more prevalent and resistance is even seen in species other than B. fragilis.…”
Section: Discussionsupporting
confidence: 87%
“…However, we were only able to detect metallo-â-lactamase activity for strains 119 and AK-2. Expression of the group 3a, class B metallo-â-lactamase encoded by the silent cfiA chromosomal gene required the location of an IS immediately upstream (Arpin et al, 2002). Edwards (1997) reported that various strains of B. fragilis that produced â-lactamases were resistant to the action of benzylpenicillin and cefoxitin and displayed moderate resistance to imipenem.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, at least one study, which used molecular genotypic methods, has reported patient-to-patient dissemination of resistant Bacteroides sp. isolates (1). In contrast, the first hypothesis may be more accurate, as at least the first case patient, due to his underlying conditions, should have had multiple hospital admissions, coupled with antibiotic treatment.…”
Section: First Case Reportmentioning
confidence: 87%